2009
DOI: 10.1007/s12012-009-9033-7
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Cardiomyopathy and Pericarditis Associated with Methylphenidate

Abstract: Methylphenidate is a potent central nervous system stimulant that exerts its effects by increasing synaptic levels of dopamine and norepinephrine. It has become key to treating attention deficit-hyperactivity disorder (ADHD) in children and adolescents. As the use of stimulant medications has ballooned in the past decade, so too has awareness of the cardiovascular complications of these drugs. Effects on heart rate and blood pressure as well as tachyarrhythmias have been well described. However, acute cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The stimulant sympathomimetics can increase blood pressure by a few millimeters of mercury, but more concerning are reports of sudden death, acute coronary syndrome, MI, stroke, and cardiomyopathy associated with their use. [187][188][189][190][191][192][193][194][195][196] Despite these case reports and small series documenting cardiac toxicity associated with stimulants, large epidemiological studies performed in children and adults treated with stimulants found no increase in the risk of serious cardiovascular events (stroke, MI, and sudden death). 197,198 Considering the case reports and well-recognized risk of sympathetic stimulation in patients with serious cardiac disease, sympathomimetic stimulants are not generally used in patients with HF.…”
Section: Neurological and Psychiatric Medicationsmentioning
confidence: 99%
“…The stimulant sympathomimetics can increase blood pressure by a few millimeters of mercury, but more concerning are reports of sudden death, acute coronary syndrome, MI, stroke, and cardiomyopathy associated with their use. [187][188][189][190][191][192][193][194][195][196] Despite these case reports and small series documenting cardiac toxicity associated with stimulants, large epidemiological studies performed in children and adults treated with stimulants found no increase in the risk of serious cardiovascular events (stroke, MI, and sudden death). 197,198 Considering the case reports and well-recognized risk of sympathetic stimulation in patients with serious cardiac disease, sympathomimetic stimulants are not generally used in patients with HF.…”
Section: Neurological and Psychiatric Medicationsmentioning
confidence: 99%
“…92,93 For the subpopulation with methylphenidate cardiotoxicity, energy drink use may increase cardiac events. 95,96 As with the ADHD stimulants, the combined effects of energy drinks and antidepressants are unknown. 94 …”
Section: Effects Of Energy Drinks On Children and Adolescents With Adhdmentioning
confidence: 99%
“…More recently, Karaman et al ( 2010) similarly reported pulmonary hypertension occurring in a patient aged 15 years, with clinical signs appearing only four days after initiation of methylphenidate therapy. Classically, methylphenidate is classed among the drugs likely to induce cardiomyopathies (Figueredo 2011; Henderson and Fischer 1995), with numerous reports published in the literature (Dadfarmay and Dixon 2009; Fischer and Baner 1977; Nymark et al 2008; Tollofsrud and Hoel 2006). …”
Section: Discussionmentioning
confidence: 99%